2010
DOI: 10.3816/ccc.2010.n.017
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Bortezomib in Combination With Standard 5-Fluorouracil and External-Beam Radiation Therapy for the Treatment of Locally Advanced or Metastatic Rectal Cancer

Abstract: Background-Standard therapy for stage II/III rectal cancer consists of a fluoropyrimidine and radiation therapy followed by surgery. Preclinical data demonstrated that bortezomib functions as a radiosensitizer in colorectal cancer models. The purpose of this study was to determine the maximum tolerated dose (MTD) of bortezomib in combination with chemotherapy and radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…One alternative approach to sensitize tumor cells to chemoradiation involves inhibition of the ubiquitin proteosome system, which is commonly aberrant in cancer (70). Several agents targeting the ubiquitin proteosome are in various phases of development (e.g.…”
Section: Sensitizing To Chemoradiation By Alternative Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One alternative approach to sensitize tumor cells to chemoradiation involves inhibition of the ubiquitin proteosome system, which is commonly aberrant in cancer (70). Several agents targeting the ubiquitin proteosome are in various phases of development (e.g.…”
Section: Sensitizing To Chemoradiation By Alternative Strategiesmentioning
confidence: 99%
“…BRCA1, MDC1, Ku80) (72), there is currently no clear evidence that bortezomib affects DNA repair. Unfortunately, initial attempts to combine bortezomib with chemoradiation have produced increased toxicity with no apparent benefit in terms of tumor reduction (70). Toxicity associated with bortezomib may be related to the deleterious effects of broadly inhibiting ubiquitin-mediated protein degradation.…”
Section: Sensitizing To Chemoradiation By Alternative Strategiesmentioning
confidence: 99%
“…No DLTs were observed. O’Neil et al [19] performed a phase I study of 5-fluorouracil and bortezomib concurrent with RT for rectal cancer. Diarrhea was the dose limiting toxicity at the 1 mg/m 2 /dose level but NF- κB activation did not appear to be suppressed at that dose.…”
Section: Discussionmentioning
confidence: 99%
“…Even more disappointing conclusions were drawn from a study of bortezomib in combination with 5-fluorouracyl and radiotherapy for the treatment of locally advanced or metastatic rectal cancer. The authors concluded that the clinical applicability of the protocol is limited and that samples of the tumors did not show any evidence of NF-jB gene suppression (O'Neil et al 2010). In conclusion, despite the fact that bortezomib was approved for treatment of multiple myeloma and mantle-cell lymphoma, its common use for therapy of solid tumors is still under extensive clinical investigation.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%